Successful bridging therapy with tirabrutinib before ASCT for relapsed primary DLBCL of the CNS complicated with PBC, cirrhosis, and pancytopenia. (2022) - Nakagawa, Noriharu; Yamano, Ruiko; Kajikawa, Sayaka; Kondo, Yukio; Okumura, Hirokazu
Abstract: The optimal therapy for relapsed primary diffuse large B-cell lymphoma (DLBCL) of the central nervous system (CNS) remains unclear. We herein report a case of relapsed primary DLBCL of the CNS complicated with primary biliary cholangitis, cirrhosis, and pancytopenia that was successfully treated with bridging therapy with tirabrutinib before autologous hematopoietic stem cell transplantation (ASCT). Tirabrutinib is well tolerated and effective for relapsed primary DLBCL of the CNS with comorbidities, including cirrhosis and pancytopenia. Tirabrutinib is a promising option as bridging therapy before ASCT.